2012
DOI: 10.1371/journal.pone.0029003
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Blood Glucose and WBC Counts in Peripheral Blood of Cases of Hand Foot and Mouth Disease in China: A Systematic Review

Abstract: BackgroundOutbreaks of Hand Foot and Mouth Disease (HFMD) have occurred in many parts of the world especially in China. We aimed to summarize the characteristics of the levels of blood glucose and white blood cell (WBC) counts in cases of HFMD in Mainland China and Taiwan, using meta-analysis based on systematic review of published articles.MethodsWe systematically reviewed published studies, from the MEDLINE and WANFANG Data, about the levels of blood glucose and WBC counts in cases of HFMD until 15th June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 25 publications
4
35
1
1
Order By: Relevance
“…Because some patients who have neurologic disease respond to treatment with highdose methylprednisolone and intravenous immune globulin, there is reason to suspect that an autoimmune phenomenon triggered by the culprit enterovirus may be the cause of many of the neurologic symptoms. 25 A 2012 meta-analysis 26 found that an elevated white blood cell count and hyperglycemia could be clinically useful in distinguishing benign from severe HFMD. In patients with benign HFMD, white blood cell counts and blood glucose values were no different from those in healthy controls.…”
Section: Neurologic and Cardiopulmonary Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because some patients who have neurologic disease respond to treatment with highdose methylprednisolone and intravenous immune globulin, there is reason to suspect that an autoimmune phenomenon triggered by the culprit enterovirus may be the cause of many of the neurologic symptoms. 25 A 2012 meta-analysis 26 found that an elevated white blood cell count and hyperglycemia could be clinically useful in distinguishing benign from severe HFMD. In patients with benign HFMD, white blood cell counts and blood glucose values were no different from those in healthy controls.…”
Section: Neurologic and Cardiopulmonary Manifestationsmentioning
confidence: 99%
“…In patients with benign HFMD, white blood cell counts and blood glucose values were no different from those in healthy controls. 26…”
Section: Neurologic and Cardiopulmonary Manifestationsmentioning
confidence: 99%
“…The pathogenesis is not completely understood but can lead to a rapid disease progression and a higher mortality rate especially in EV71-infected children [5][6][7]. Specific biomarkers were identified to estimate the severity of HFMD cases [8][9][10]. Hyperglycemia and leukocytosis are two important characteristics in severe patients, and blood glucose and peripheral white blood cell (WBC) count seem to change with the severity of the disease [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory abnormalities are commonly observed in children at early stage of severe disease, which include a raised white cell count with relative neutrophilia, hyperglycaemia and elevated CSF lactate [16,24,25]. Recently, a systematic review including 37 studies, mostly from Mainland China and Taiwan, indicated the prevalence of WBC counts and leukocytosis increased with the severity of the illness [26]. Although these indicators seem more likely to present in severe HFMD cases, their diagnostic value is limited for clinically predicting children at high risk of severe HFMD, particularly in primary care settings, as leukocytosis and hyperglycemia appear later in the course of fulminant cardiorespiratory failure in our opinion.…”
Section: Discussionmentioning
confidence: 99%